2021
DOI: 10.1103/physrevmaterials.5.014410
|View full text |Cite
|
Sign up to set email alerts
|

Rhombohedral distortion-driven ferroelectric order and exchange bias effect in geometrically frustrated ZnFe2O4

Abstract: The rhombohedral distortion-driven occurrence of the spontaneous electric polarization at a reasonably high temperature (T ) and an exchange bias (EB) effect below the antiferromagnetic (AFM) Néel temperature (T N ) are revealed in ZnFe 2 O 4 . We observe the magnetic memory effect, suggesting a cooperative glassy magnetic state below T N . The phase separation between the long-range AFM and the glassy magnetic component leads to the EB effect below T N . The synchrotron diffraction studies confirm a structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
(109 reference statements)
2
4
0
Order By: Relevance
“…227) represents a polar structure, exhibiting the highest symmetry among the various structures considered. This finding aligns with the rhombohedral distortion-driven structural transition to R3m structure from F d 3m, which was associated with the observed FE order in ZnFe 2 O 4 [51]. A satisfactory Rietveld refinement of the diffraction pattern at 175 K, employing the R3m space group, is presented in Fig.…”
Section: Resultssupporting
confidence: 84%
“…227) represents a polar structure, exhibiting the highest symmetry among the various structures considered. This finding aligns with the rhombohedral distortion-driven structural transition to R3m structure from F d 3m, which was associated with the observed FE order in ZnFe 2 O 4 [51]. A satisfactory Rietveld refinement of the diffraction pattern at 175 K, employing the R3m space group, is presented in Fig.…”
Section: Resultssupporting
confidence: 84%
“…The structural study attempts to extract knowledge from the crystallography and understanding origins of the different multifunctional properties of the system. The structural correlation to the electrical and magnetic properties has been recently found crucial in few systems, which provides rich consequences in solid state such as colossal magnetoresistance [1], giant magnetocaloric effect [2], Griffiths phase singularities [3], spontaneous ferroelectric order [4,5], multiferroic order [6]. In the current observation we report important structural correlations to the various unexplored multifunctional properties of YbCrO 4 .…”
Section: Introductionsupporting
confidence: 55%
“…The decrease in current with increasing H is consistent with the variation of P with H as shown in the inset of figure 3(f). It is interesting to point out that the ME coupling is observed below ∼ 90 K, which is much above the magnetic ordering temperature at 25 K. The dominant short-range ordering above the ferrimagnetic ordering associated with the progressive structural distortion below T F E may correlate the significant ME consequence at much higher temperature, as recently observed in few occasions [4,7,40,41,42].…”
Section: Resultsmentioning
confidence: 69%
“…Moreover, Suzuki et al reported large magneto-capacitance (∼10% at 14 T) and magnetization coupled dielectric relaxation in polycrystalline ZFO [49]. These results are further supported by very recent observations on ferroelectric behaviour linked to the rhombohedral distortion (R3m space group) from the cubic structure, across 110 K, along with the glassy AFM character and magnetic memory effects below T N in addition to a weak exchange bias effect [50]. Nevertheless, the high field susceptibility data and neutron scattering measurements of single crystalline ZFO by Kamazawa et al reported the absence of long-range order and diffuse magnetic scattering around the nuclear Bragg peaks which disappear under the application of an external magnetic field of magnitude ∼30 kOe [51][52][53].…”
Section: Introductionmentioning
confidence: 55%